Downregulation of microRNA-199a-5p alleviated lidocaine-induced sensory dysfunction and spinal cord myelin lesions in a rat model. (1st January 2021) - Zhang, Zhong; Wang, Jian; Song, Zongbin; Wang, Yunjiao; Cheng, Zhigang; Guo, Qulian; Wang, E.; Jian, Yanping; Wu, Lei
Graphical abstract: Highlights: Lidocaine induced myelin lesions of the spinal cord and sensory dysfunction in rats. Lidocaine increases miR-199a-5p expression and decreases MYRF expression in spinal cord. Inhibition of miR-199a-5p expression alleviated lidocaine-induced sensory dysfunction and spinal cord myelin lesions. MiR-199a-5p is involved in lidocaine-induced spinal cord myelin lesions may via regulating MYRF. Abstract: Lidocaine induces neurotoxicity in the spinal cord, but the underlying mechanisms remain unclear. In this study, we evaluated the effects of miR-199a-5p on 10 % lidocaine neurotoxicity. Increased expression of miR-199a-5p in the spinal cord of rats treated with 10 % lidocaine was assessed by qRT-PCR. Furthermore, after miR-199a-5p antagomir administration, the sensory dysfunction and myelin sheath lesions (evaluated by semithin sections stained with toluidine blue, electron microscopy, g-ratios and myelin thickness) induced by 10 % lidocaine were alleviated. Myelin regulatory factor (MYRF), a key molecule of myelin sheath development, was predicted to be a target gene of miR-199a-5p by the TargetScan and miRBase databases. MYRF and its downstream factors myelin basic protein (MBP), proteolipid protein (PLP) and myelin oligodendrocyte glycoprotein (MOG) were significantly decreased after intrathecal 10 % lidocaine administration. Moreover, these changes were reversed after miR-199a-5p antagomir administration. FISH-immunofluorescence showed coexpression of miR-199a-5p and MYRF in the spinal cord white matter of rats. A luciferase reporter assay further demonstrated the functional association between miR-199a-5p and MYRF. Overall, miR-199a-5p upregulation is involved in 10 % lidocaine-induced spinal cord toxicity through regulation of MYRF. Therefore, downregulating miR-199a-5p expression may be a potential strategy to ameliorate spinal cord neurotoxicity induced by 10 % lidocaine.